2012
DOI: 10.1002/jgm.1647
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of chondroitin sulfate‐coated ternary granulocyte macrophage‐colony‐stimulating factor plasmid complex for ovarian cancer

Abstract: These findings suggest that GM-CSF/PEI coated with 10-kDa chondroitin sulfate has the potential for use in gene therapy of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Furthermore, Hagiwara et al reported that a ternary complex of pDNA/chitosan/CS ( Figure 5A) exhibited high cellular uptake via micropinocytosis [60], and strongly inhibited tumor growth in Huh-7 tumor xenografts by intratumoral injection of the complexes with pDNA encoding herpes simplex virus thymidine kinase (HSV-tk) [61]. Hamada et al reported that intraperitoneal injection of ternary complex ( Figure 5A) of pDNA/PEI/CS encoding murine granulocyte macrophage-colony- stimulating factor (mGM-CSF) prolonged survival in an intraperitoneal ovarian tumor model [62]. In addition, intratumoral injection of the ternary complex achieved mouse survival rates of 100% in a subcutaneous tumor model.…”
Section: Lo Et Al Reported That Cs-modi Ied Pei/pdna (mentioning
confidence: 99%
“…Furthermore, Hagiwara et al reported that a ternary complex of pDNA/chitosan/CS ( Figure 5A) exhibited high cellular uptake via micropinocytosis [60], and strongly inhibited tumor growth in Huh-7 tumor xenografts by intratumoral injection of the complexes with pDNA encoding herpes simplex virus thymidine kinase (HSV-tk) [61]. Hamada et al reported that intraperitoneal injection of ternary complex ( Figure 5A) of pDNA/PEI/CS encoding murine granulocyte macrophage-colony- stimulating factor (mGM-CSF) prolonged survival in an intraperitoneal ovarian tumor model [62]. In addition, intratumoral injection of the ternary complex achieved mouse survival rates of 100% in a subcutaneous tumor model.…”
Section: Lo Et Al Reported That Cs-modi Ied Pei/pdna (mentioning
confidence: 99%
“…Chondroitin sulfate has been widely used in drug delivery as a hydrophilic component of self-assembled nanocarriers (33)(34)(35)(36)(37)(38)(39). In addition, due to the anionic charge and the ability to bind to CD44, chondroitin sulfate has been used in combination with polymeric gene carriers to reduce the cationic charge (40)(41)(42)(43)(44)(45)(46) and improve the target specificity (45)(46)(47). The chondroitin sulfate associated with cationic gene carriers is also shown to modify intracellular trafficking of the gene complex (promote endosomal escape and accumulation at the nuclear periphery) in favor of gene transfection (48).…”
Section: Chondroitin Sulfatementioning
confidence: 99%
“…Alternatively, CS is used to coat a DNA–PEI complex to shield the cationic charge [107,108]. A ternary complex consisting of DNA, PEI and CS showed greater in vitro gene transfection efficiency and tumor accumulation than the DNA–PEI complex [108].…”
Section: Chondroitin Sulfatementioning
confidence: 99%
“…A ternary complex consisting of DNA, PEI and CS showed greater in vitro gene transfection efficiency and tumor accumulation than the DNA–PEI complex [108]. A ternary complex consisting of CS, PEI and DNA encoding mGM-CSF also inhibited the growth of intraperitoneal and subcutaneous tumors in a syngeneic mouse model to a greater extent than a binary complex of PEI and mGM-CSF DNA or another ternary complex using high-molecular-weight HA instead of CS [107]. …”
Section: Chondroitin Sulfatementioning
confidence: 99%